Flexible and transparent piezoelectric loudspeaker - M. Shehzad (Nature Portfolio, 2021)
Abstract The simple structure of flexible piezoelectric polymers implies promise innumerous applications, such as transparent loudspeakers. In this study, we fabricated and characterized a prototype loudspeaker device. The loudspeaker was fabricated using a straightforward method of sandwiching a film of copolymer blend between a pair of flexible ITO substrates, which served as top and bottom electrodes. The dependence of acoustic properties of the devices was investigated in accordance with d 33 and piezoresponse force microscopy (PFM). In this study, we examine the sound pressure level (SPL) and sound intensity (SI) of devices featuring 0.5 ≤ α ≤ 0.9 blends, with an active area of 6.5 cm × 5 cm at 100 Vpp applied voltage. Here we report SPL of 96 dB and SI of 3.98 m Wm−2 for an α = 0.7 blend at 100 Vpp. Our results are helpful in developing flexible, transparent piezoelectric polymers and in the development of lightweight, transparent loudspeaker devices.